1998
DOI: 10.1159/000013979
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of Magnetic Resonance Imaging at 4 Months of Adjusted Age in Infants after a Perinatal Neurologic Insult

Abstract: The aim of this prospective study was to evaluate the predictive significance of magnetic resonance imaging (MRI) performed at 4 months of corrected age in 60 neonates after a perinatal neurologic insult. Follow-up ranged from 2 to 5 years of chronological age. MRI examination was normal in 10; isolated external hydrocephalus was found in 15 infants. Twenty-three of these infants developed normally. Focal or multifocal lesions were shown in 6 infants, of whom 2 developed normally. Diffuse brain involvement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Although rare, MRI beyond the first month after birth is sometimes performed to assess myelination and the evolution of lesions that were seen on the neonatal scan, or when infants were too ill to be scanned within the first weeks after birth [101]. There are studies that have suggested that MRI performed at 2-5 months of age has a predictive significance for later neurodevelopmental outcomes, but literature on MRI at this age is scarce [101][102][103].…”
Section: Repeat Mrimentioning
confidence: 99%
“…Although rare, MRI beyond the first month after birth is sometimes performed to assess myelination and the evolution of lesions that were seen on the neonatal scan, or when infants were too ill to be scanned within the first weeks after birth [101]. There are studies that have suggested that MRI performed at 2-5 months of age has a predictive significance for later neurodevelopmental outcomes, but literature on MRI at this age is scarce [101][102][103].…”
Section: Repeat Mrimentioning
confidence: 99%
“…Cerebral palsy in pre-term infants was predicted by altered MRI signals associated with hemorrhagic and white matter lesions. In term infants, T2-signal abnormalities, more then T1 abnormalities, predicted an unfavorable outcome, documenting poor myelination and focal/multifocal lesions on subsequent studies for children with subsequent neurologic insults [78].…”
Section: Neuroimagingmentioning
confidence: 93%
“…Most studies included only infants with gestational age ≥36.0 weeks (n = 8, 67%). In three studies, only a subset of the study population had a history of perinatal asphyxia [16][17][18]. Age at last follow-up assessment ranged from 3 months to 17 years of age.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies used the Griffiths Mental Development Scales (n = 4) and/or different editions of the Denver Developmental Screening Test (n = 4) and the Bayley Scales of Infant and Toddler Development (n = 3) to assess neurodevelopmental outcomes. All twelve studies analyzed infants with a later MRI performed within 18 months after birth [10,[16][17][18][19][20][21][22][23][24][25][26] and three studies also described a subset of infants with MRI performed at 18-24 months after birth [10,16,24]. For six papers, the data as presented by the study were re-analyzed in SPSS, as a complete statistical analysis was not provided in the article.…”
Section: Study Characteristicsmentioning
confidence: 99%